The Balanced Scorecard as a Strategy-Evaluation Tool: The Effects of Implementation Involvement and a Causal-Chain Focus - Tayler, William B. (The Accounting Review, 2010)
ABSTRACT: Using an experiment, I examine whether involvement in scorecard implementation can mitigate the effects of motivated reasoning that occur when the scorecard is framed as a causal chain rather than merely as a balanced set of measures. Psychological research on motivated reasoning suggests that managers will evaluate and interpret data in ways consistent with preferences, increasing their tendency to arrive at conclusions that are consistent with their desired conclusions (Kunda 1990). Consistent with that research, results of my study show that managers who are involved in selecting strategic initiatives perceive those initiatives as having been more successful than managers who are not involved in the initiative-selection process (holding constant actual scorecard performance). Results suggest further that simply framing the scorecard as a causal chain is not sufficient to mitigate these effects. However, framing the scorecard as a causal chain, in conjunction with involving managers in the selection of scorecard measures, mitigates the effects of motivated reasoning tied to manager involvement in initiative selection.